2020
DOI: 10.1183/13993003.02279-2019
|View full text |Cite
|
Sign up to set email alerts
|

Survival and course of lung function in the presence or absence of antifibrotic treatment in patients with idiopathic pulmonary fibrosis: long-term results of the INSIGHTS-IPF registry

Abstract: RationaleThere is a paucity of observational data on antifibrotic therapy for idiopathic pulmonary fibrosis (IPF).ObjectiveWe aimed to assess the course of disease of IPF patients with and without antifibrotic therapy under real-life conditions.MethodsWe analysed data from a non-interventional, prospective cohort study of consecutively enrolled IPF patients from 20 ILD expert centres in Germany. Data quality was ensured by automated plausibility checks, on-site monitoring, and source data verification. Propens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
106
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 28 publications
12
106
1
11
Order By: Relevance
“…Thus, approximately 65% of the patients received anti-fibrotic treatment in our study, which is considerably more than in Germany (44%) [9], Finland (26%) [10], and Australia (23%) [6]. The present study shows that patients on anti-fibrotic therapy appear to survive longer than untreated patients, a result similar to what other registries have reported [6,8,20]. In order to avoid a potential bias in mortality analysis, Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, approximately 65% of the patients received anti-fibrotic treatment in our study, which is considerably more than in Germany (44%) [9], Finland (26%) [10], and Australia (23%) [6]. The present study shows that patients on anti-fibrotic therapy appear to survive longer than untreated patients, a result similar to what other registries have reported [6,8,20]. In order to avoid a potential bias in mortality analysis, Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive fibrosing interstitial lung disease (ILD) of unknown cause [1][2][3].The disease is characterized by an aberrant accumulation of fibrotic tissue in the lung parenchyma, resulting in extensive alterations of lung structure and function and leads finally to respiratory failure and death [2,4,5]. Long-term observational studies in clinically diverse IPF populations from all over the world are increasing [1,[6][7][8][9][10][11][12][13][14][15] and provide us with important information on disease behaviour, management, and effectiveness of approved treatments.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of real-world data on post-exacerbation survival in patients treated with nintedanib or pirfenidone. However, data from the European IPF Registry (eurIPFreg), the INSIGHTS-IPF registry (Germany) and the Australian Idiopathic Pulmonary Fibrosis Registry suggest that patients with IPF who receive antifibrotic treatment have better overall survival than patients with IPF who do not receive nintedanib or pirfenidone [23,116,117]. Post-hoc analyses of the INPULSIS trials observed an association between nintedanib treatment and a numerical reduction in mortality following an acute exacerbation [45,47].…”
Section: Use Of Nintedanib In Real-world Clinical Practicementioning
confidence: 99%
“…The real-life EMPIRE registry showed that patients with usual interstitial pneumonia (UIP) and antineutrophil cytoplasmic antibody (ANCA)-positive ILD without signs of vasculitis had some distinct features but showed a similar survival curve to the ANCA-negative patients with IPF [9]. The INSIGHTS-IPF registry demonstrated that IPF patients, irrespective of antifibrotic therapy, remained relatively stable in terms of FVC and diffusing capacity of the lung for carbon monoxide (D LCO ) over a 2-year period, but the risk of death was 37% lower in patients on antifibrotic treatment [10]. The DIAMORFOSIS study, an international survey about the diagnostic and therapeutic management of patients with IPF and lung cancer, showed that there is wide variation in current practice, highlighting the need for a consensus statement on this topic.…”
Section: Idiopathic Interstitial Pneumoniasmentioning
confidence: 99%